Qualitative welfare risks of cows offered to a Dutch mobile slaughter unit - Ursinus, Winanda W.; Voogt, Annika M.; Bongers, Johan H.; Sijm, Dick T. H. M. (Frontiers in Animal Science, 2023)
In the Netherlands, a pilot was initiated of a mobile slaughter unit (MSU) for the killing of cull dairy cattle not fit for transport but suitable for slaughter, in order to save valuable meat. The Office for Risk Assessment & Research (BuRO) was asked to assess the risks for animal welfare. As a thorough risk assessment would have been very time consuming, a qualitative framework was used instead. The goal of the current study was to qualitatively describe the relevant risks for cow welfare involved in the use of an MSU compared with current practice by carrying out a rapid comparative risk assessment of animal welfare. The assessment framework consisted of the following steps: identification and description of scenarios, followed by assessment and comparison of the most relevant animal welfare risks in these scenarios, including hazard identification, hazard characterization, exposure, and characterization of the risk to animal welfare. Two main scenarios were identified, one with and one without an MSU. The second scenario was split into three sub-scenarios: killing on the farm/in a housing unit, emergency slaughter, and conventional transport to the slaughterhouse. The most relevant risks associated with operating an MSU were as follows: leaving the cow alive on the farm when it was not fit for slaughter; forcing the cow to walk to and into the MSU (however, this risk is likely higher under conventional transport of unfit cows); and insufficient stunning and bleeding, leading to questionable unconsciousness (however, this risk is likely higher in an emergency slaughter scenario). The MSU is a means of preventing the exacerbation of welfare deterioration in cows that are unfit for transport but fit for slaughter, and it reduces exposure to stressors (hazards) that are conventionally present during transport and at a stationary slaughterhouse. This rapid comparative risk assessment of animal welfare supported swift decision-making: the national competent authority (i.e., the NVWA in the Netherlands) and policymakers were able to improve and develop risk-mitigating actions and to decide on allowing the use of an MSU. When appropriately designed and used, and with sufficient supervision, mobile slaughter facilities can reduce welfare risks in cull dairy cows that are unfit for transport but fit for slaughter.